2021
DOI: 10.3389/fphar.2021.677943
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Pharmacist-Led Remote Warfarin Management Model Using a Smartphone Application (Yixing) in Improving Patients’ Knowledge and Outcomes of Anticoagulation Therapy

Abstract: Background: The management of warfarin-treated patients has been recognized as a challenge due to narrow therapeutic range and food and drug interactions in warfarin therapy. We aim to evaluate the effect of a pharmacist-led remote warfarin management model using a smartphone application (app) on anticoagulation therapy.Methods: Eligible patients who had received warfarin therapy after mechanical heart valve replacement were enrolled. The intervention group was offered a pharmacist-led remote warfarin manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…It includes functions such as reminders for drug intake, a personal health record, an educational program to raise the patient’s awareness, and online counseling. The authors conducted a prospective study with 100 patients who had received a valve replacement; patients were distributed equally into an intervention group, who were using the Yixing app after receiving app-based training, and a control group, who would receive oral medication training but no further support after being discharged from the hospital [ 16 ]. The results revealed that using the app could increase the patient’s awareness and days spent within the therapeutic range but did not have an influence on the number of days that warfarin was taken correctly or the incidence of anticoagulation-related complications.…”
Section: Resultsmentioning
confidence: 99%
“…It includes functions such as reminders for drug intake, a personal health record, an educational program to raise the patient’s awareness, and online counseling. The authors conducted a prospective study with 100 patients who had received a valve replacement; patients were distributed equally into an intervention group, who were using the Yixing app after receiving app-based training, and a control group, who would receive oral medication training but no further support after being discharged from the hospital [ 16 ]. The results revealed that using the app could increase the patient’s awareness and days spent within the therapeutic range but did not have an influence on the number of days that warfarin was taken correctly or the incidence of anticoagulation-related complications.…”
Section: Resultsmentioning
confidence: 99%
“…To assist clinicians with individualizing warfarin therapy, we simulated individualized warfarin dosing based on LSTM_INR. The trend of using mobile applications or electronic systems for anticoagulation is likely more suitable for long-term individualized therapy and anticoagulant self-management ( 27 , 28 ). Thus, we developed an application (AI-WAR) in which we embedded these were embed in.…”
Section: Discussionmentioning
confidence: 99%
“…As in most studies, the Internet-based group showed a significantly higher TTR, and anticoagulation complications, including bleeding and embolic events, were less frequent in the Internet-based group than in the conventional group (6.94% vs. 12.74%; P = 0.01). Jiang et al ( 63 ) developed an APP named “Yixing”, which was not connected to a portable clotting instrument. Compared with follow-up using telephone remote management, this APP established a communication platform for patients and pharmacists, facilitating timely management of warfarin, improving efficiency, and increasing fraction of TTR (FTTR).…”
Section: Mobile Internet and Anticoagulant Self-managingmentioning
confidence: 99%